Effects of saliency, not global dominance, in patients with left parietal damage. - Mevorach, C; Humphreys, G; Shalev, L (2006)
Neuropsychological and functional imaging studies have shown a general right hemisphere advantage for processing global visual information and a left hemisphere advantage for processing local information. There is also evidence for the left parietal lobe being important for switching attention between local and global levels. Here we examined whether the left parietal lobe is associated with another aspect of attentional control over hierarchical visual processing; namely, ignoring the irrelevant aspect of the stimulus when it is more salient than the target attribute. In experiment 1 a group of left parietal patients were abnormally affected by a salient local stimulus that significantly interfered with their ability to identify global shapes. This effect was reversed in experiment 2 when small sized compound letters were used (where the global shape was more salient than the local letters). The patients then had difficulty ignoring the global shape. Experiments 3 and 4 demonstrated that the failure to accurately identify global form in experiment 1 could not be attributed to a difficulty in spreading attention across a large area. Finally, in experiment 4 the effect of a salient irrelevant stimulus was significantly attenuated when the irrelevant level did not map onto a response. The data indicate that damage to the left parietal lobe disrupts the ability to select attributes of stimuli that have low salience when other attributes have high salience for the task.